2019
DOI: 10.2196/14519
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Physical Symptoms in Patients With Tinnitus: International Web-Based Survey

Abstract: Background Tinnitus, or ringing in the ears, is a phantom perception of sound in the absence of overt acoustic stimulation. Many patients indicate that the perception of their tinnitus is not constant and can vary from moment to moment. This tinnitus fluctuation is one of the diagnostic criteria for somatosensory tinnitus (ST), a tinnitus subtype that is influenced by cervical spine or temporomandibular dysfunctions, although various factors have been reported to cause fluctuations in tinnitus, suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
1
8
2
3
Order By: Relevance
“…When this somatosensory influence is one of the major influencing factors, a patient's tinnitus is called somatic or somatosensory tinnitus (ST). This type of tinnitus is present in 12% to 43% of tinnitus patients, depending on the setting (primary care, tertiary care, open population) and diagnostic criteria for ST [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…When this somatosensory influence is one of the major influencing factors, a patient's tinnitus is called somatic or somatosensory tinnitus (ST). This type of tinnitus is present in 12% to 43% of tinnitus patients, depending on the setting (primary care, tertiary care, open population) and diagnostic criteria for ST [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic oromandibular dystonia [69], often associated with bruxism, occurs after TBI. Furthermore, it has been shown that bruxism contributes not only to post-TBI headaches [70] but is also correlated with the presence of tinnitus [71]. While dentists are perhaps most likely to identify bruxism because of secondary tooth wear [72], TBI patients might unfortunately not be guided to include oral health professionals on their care team, so specifically asking patients about bruxism could reveal a treatable and impactful diagnosis.…”
Section: Oralmentioning
confidence: 99%
“…This fluctuation of tinnitus can depend on various factors, such as stress ( Mazurek et al, 2015 ), emotional state ( Probst et al, 2016 ), anxiety ( Bhatt et al, 2017 ), depression ( Bhatt et al, 2017 ), cervical spine dysfunction ( Michiels et al, 2015 ), and temporomandibular disorders (TMD) ( Buergers et al, 2014 ). In these last two cases, tinnitus is called somatosensory (or somatic) tinnitus (ST), which is present in 12–43% of patients with subjective tinnitus ( Michiels et al, 2015 , 2019a ). A physiological explanation for ST can be found in animal studies where connecting fibers between the dorsal cochlear nucleus (DCN) and the somatosensory nuclei are found ( Kanold and Young, 2001 ).…”
Section: Introductionmentioning
confidence: 99%